Reading Heresy: Religion and Dissent in Literature and Art - Erickson, Gregory (De Gruyter, Inc., 2017)
Heresy studies is a new interdisciplinary, supra-religious, and humanist field of study that focuses on borderlands of dogma, probes the intersections between orthodoxy and heterodoxy, and explores the realms of dissent in religion, art, and literature. Free from confessional agendas and tolerant of both religious and non-religious perspectives, heresy studies fulfill an important gap in scholarly inquiry and artistic production. Divided into four parts, the volume explores intersections between heresy and modern literature, it discusses intricacies of medieval heresies, it analyzes issues of heresy in contemporary theology, and it demonstrates how heresy operates in artistic and literature creativity today. Rather than treating matters of heresy, blasphemy, unbelief, dissent, and non-conformism as subjects to be shunned or naively championed, the essays in this collection chart a middle course, energized by the dynamics of heterodoxy, dissent, and provocation, yet shining a critical light on both the challenges and the revelations of disruptive kinds of thinking and acting. Gregory Erickson, New York University, U.S.A and Bernard Schweizer, Long Island University, New York, U.S.A.